The Application and Innovation of Multimodal Digital Public Art in Urban Spaces (Journal of Global Arts Studies, 2025)
Background: With the rapid advancement of digital media technology, multimodal digital public art has increasingly expanded its applications in urban spaces, emerging as an innovative approach to enhancing urban aesthetics and the interactivity of public art. Objective: This study aims to explore the value and development trends of multimodal interaction technology in digital public art, focusing on its impact on urban aesthetics, interactivity, and public engagement. Methods: Through a combination of literature review and case analysis, the study defines the concepts of multimodal interaction and digital public art, examines their specific applications in urban public spaces, transportation hubs, commercial areas, and digital art exhibitions, and summarizes the practical performance of related technologies and design methodologies. Results: The findings indicate that multimodal interaction technology, by integrating digital tools and sensory engagement, significantly enhances the interactivity and experiential quality of digital public art, improves the aesthetic value of urban spaces, and provides the public with a more active role in artistic participation. Conclusion: Multimodal digital public art plays a vital role in urban spaces. Its future development should emphasize deep integration with urban planning, optimization of technological designs to increase public participation, adherence to sustainable development principles, and strengthened policy support and resource allocation to promote its widespread application and innovative growth in modern urban environments.
Keywords: Digital Public Art; Multimodal Interaction; New Media Art; Urban Space